Preparation, characterization and mechanical properties of rare-earth-based nanocomposites - Musbah S.S.; Radojević V.; Radović I.; Uskoković P.S.; Stojanović D.B.; Dramićanin M.; Aleksić R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This study reports research related to different preparation methods and characterization of polymer nanocomposites for optical applications. The Eu-ion doped Gd2O3 nanophosphor powder with different nanoparticle content was embedded in the matrix of PMMA. Preparation was carried out by mixing molding (bulk), electrospinning (nanofibers) and solution casting (thin films) with neat particles and particles coated with AMEO silane. Among the pros and cons for proposed methods, the mixing molding enables to avoid solvent use while the best deagglomeration and nanoparticle distribution is gained using the electrospinning method. The results of dynamic mechanical analysis (DMA) and nanoindentation revealed that the storage modulus of the composites was higher than that of pure PMMA and increased with nanophosphor content. Surface modification of particles improved the mechanical properties of nanocomposites.